INFLUENCING CONSUMER PREFERENCE AND SATISFACTION TOWARDS BUYING BEHAVIOUR OF KITCHEN APPLIANCE PRODUCTS IN KRISHNAKIRI DISTRICT - Elavarasi, G; Pasupathi, V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Every business in India, particularly in the country's largest cities, is attempting to survive on its platform as best it can under the current circumstances in order to reach the target number of prospective clients. The world economy will inevitably shift, and liberalisation is essential to our nation. With its extensive and excellent product line, the premier multinational company has joined the Indian market and is already playing a significant role. We understand that our "Customer is the King" and that the Indian market is expanding with a superior product line in electronic home appliances as compared to the global market. Customers are sufficiently aware and sound to make the best choices when it comes to purchasing the chosen brand of home appliances in order to meet the necessary objective. Without home appliances, a contemporary house is incomplete, particularly in large cities and metropolitan regions. In large metropolises, electronic home appliances are seen as a boon as they significantly reduce the amount of time needed for the majority of domestic household chores. Thus, the researchers took into consideration their study on the purchasing habits of consumers in Krishnagar District, Tamil Nadu, with regard to electronics and household appliances. Products related to home appliances such as air coolers, refrigerators, washers, microwaves, and televisions are included in this study. 253 respondents in Krishnagar were chosen for this study using an expedient sampling technique. This study employed a demographic research design, using a questionnaire as a means of gathering data from participants. Additionally, data segmentation will be used in the study. The conclusion reached was that while price, quality, offer, and appliance features empowered the consumer to purchase the appliance, demographic characteristics also influenced the consumer's decision to purchase.